Experimental investigation of a reticulated porous alumina heat exchanger for high temperature gas heat recovery. (22nd January 2015) - Banerjee, A.; Bala Chandran, R.; Davidson, J.H.
Abstract: The present study presents an experimental study of a prototype counter-flow heat exchanger designed to recover sensible heat from inert and reactive gases flowing through a high temperature solar reactor for splitting CO2. The tube-in-tube heat exchanger is comprised of two concentric alumina tubes, each filled with reticulated porous alumina with a nominal porosity of 80% and pore density of 5 pores per inch ( ppi ). The RPC provides high heat transfer surface area per unit volume (917 m −1 ) with low pressure drop. Measurements include the permeability, inertial coefficient, overall heat transfer coefficient, effectiveness and pressure drop. For laminar flow and an inlet gas temperature of 1240 K, the overall heat transfer coefficients are 36–41 W m −2 K −1 . The measured performance is in good agreement with a prior CFD model of the heat exchanger. Highlights: A ceramic heat exchanger provides gas-phase heat recuperation for a solar thermochemical reactor. Alumina reticulated porous ceramic (RPC) provides high surface area and low pressure drop. Heat transfer and pressure drop are measured at temperatures up to 1240 K. RPC provides a 9-fold increase in heat transfer compared to bare tubes.